1994
DOI: 10.1177/42.3.8308256
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of heating modes in rapid fixation techniques for electron microscopy.

Abstract: Recent studies have established that microwave irradiation during aldehyde fmaon of electron microscopy specimens can reduce fmtion times substantially. Similar reductions in duration of histochemical and light microscopy procedures have been reported. Both thermal and non-thermal effects of miaowam have been proposed to explain these dramatic dwclses in processing time. possible the-rmal effects indude increases in fmtive diffusion and reaction rates and inaeased formation of glutaraldehyde monomers. Proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…This is contrary to conventional heating, which begins outside the sample (Leonard and Shepardson, 1994; Giberson and Demaree, 1995; Kok and Boon, 2003; De La Hoz et al, 2005; Schroeder et al, 2006; Zechmann and Zellnig, 2009). Due to this phenomenon, tissue processed in the microwave promotes deeper penetration of reagents.…”
Section: Discussionmentioning
confidence: 91%
“…This is contrary to conventional heating, which begins outside the sample (Leonard and Shepardson, 1994; Giberson and Demaree, 1995; Kok and Boon, 2003; De La Hoz et al, 2005; Schroeder et al, 2006; Zechmann and Zellnig, 2009). Due to this phenomenon, tissue processed in the microwave promotes deeper penetration of reagents.…”
Section: Discussionmentioning
confidence: 91%
“…Curiously, previous experiments of microwave-enhanced fixation paid little attention to the reduction of the fixative concentration, setting it at similar levels as those used in conventional procedures (Leonard and Shepardson, 1994;Login and Dvorak, 1988;Login et al, 1990;Ohtani, 1991;Wild, 1991). It is true that proposals were made some years ago in favor of the ability of microwave irradiation to act as the only fixation agent, due to its effects on protein coagulation.…”
Section: Discussionmentioning
confidence: 94%
“…While the reason why microwave irradiation of a polar substance results in energy absorption and heating is evident and the physical mechanisms that are responsible for heat production are well understood (Boon and Kok, 1988), it is not clear whether heating is the only cause of the enhancing effect of microwaves on fixation or if some additional effects are involved and, in this case, what might be their nature. In fact, this remains the main open discussion on this topic (Feirabend et al, 1992;Kok and Boon, 1990b;Leonard and Shepardson, 1994;Medina et al, 1995;Wild, 1991). Otherwise, an excess of heat applied to the sample by microwave irradiation is commonly considered unacceptable, since it results in protein denaturation; in general, published procedures of microwave-enhanced fixation recommend keeping the temperature below 50°C (see also Moriguchi et al, 2002).…”
Section: Introductionmentioning
confidence: 95%
“…Conflicting ideas about the nature of microwave fixation remain on the mechanisms of the heating versus the microwave effects. The heating effect is believed to improve penetration of reagents and speed up fixation 44 . Other publications have suggested that the microwave effects were non-thermal based on a study of globular proteins 45 and an increased rate of bone demineralization independent of temperature 46 .…”
Section: Experimental Designmentioning
confidence: 99%